Recovery methods to reduce fatigue among athletes: A systematic review and future directions - Yoda, I Ketut; Tisna MS, Gede Doddy; Suwiwa, I Gede; Kusuma, Ketut Chandra Adinata; Junior, Nelson Kautzner Marques (Journal Sport Area, 2024)
Background Problems: The recovery process plays an important role in maintaining athletic performance and preventing fatigue among players. Research Objectives: This systematic review aims to provide a comprehensive overview of the current research on athlete fatigue recovery, including the various methods used to enhance recovery, the limitations of existing studies, and potential areas for future research. Methods: This study was reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). We designed the study using the PICOS strategy. We sourced the literature from established research sources in the Scopus databases. The final data used for this study consisted of 24 articles. Findings and Results: The main findings confirmed that aquatic therapies, such as hot-and-cold-water immersion (HWI) and cold-water immersion (CWI), along with a number of other alternative methods, provide a strong foundation for improving athletes' recovery and performance. In addition, various novel therapies such as curcumin supplements, electrostimulation, and high-intensity interval training (HIT) also offer great potential for accelerating athletes’ recovery. Conclusion: The findings from this study highlight various recovery methods that can help reduce athletes’ fatigue after competition or training. This study also noted limitations and provided suggestions for future research, guiding researchers to further understand and improve athlete recovery holistically.